The Kynurenine Pathway Is Upregulated by Methyl‐deficient Diet and Changes Are Averted by Probiotics. Issue 9 (24th March 2021) - Tillmann, Sandra; Awwad, Hussain M.; MacPherson, Chad W.; Happ, Denise F.; Treccani, Giulia; Geisel, Juergen; Tompkins, Thomas A.; Ueland, Per Magne; Wegener, Gregers; Obeid, Rima
Abstract : Scope: Probiotics exert immunomodulatory effects and may influence tryptophan metabolism in the host. Deficiency of nutrients related to C1 metabolism might stimulate inflammation by enhancing the kynurenine pathway. This study used Sprague Dawley rats to investigate whether a methyl‐deficient diet (MDD) may influence tryptophan/kynurenine pathways and cytokines and whether probiotics can mitigate these effects. Methods and Results: Rats are fed a control or MDD diet. Animals on the MDD diet received vehicle, probiotics ( L. helveticus R0052 and B. longum R0175), choline, or probiotics + choline for 10 weeks ( n = 10 per group). Concentrations of plasma kynurenine metabolites and the methylation and inflammatory markers in plasma and liver are measured. Results: MDD animals (vs controls) show upregulation of plasma kynurenine, kynurenic acid, xanthurenic acid, 3‐hydroxyxanthranilic acid, quinolinic acid, nicotinic acid, and nicotinamide (all p < 0.05). In the MDD rats, the probiotics (vs vehicle) cause lower anthranilic acid and a trend towards lower kynurenic acid and picolinic acid. Compared to probiotics alone, probiotics + choline is associated with a reduced enrichment of the bacterial strains in cecum. The interventions have no effect on inflammatory markers. Conclusions: Probiotics counterbalance the effect of MDD diet and downregulate downstream metabolites of the kynurenine pathway. Abstract : A methyl‐deficient diet (MDD) causes higher serotonin and upregulation of the kynurenine pathway and is associated with weight reduction in the young animals. Intervention with probiotics ( L. helveticus and B. longum ) lowers plasma kynurenine metabolites. Intervention with choline causes slight downregulation of the kynurenine upstream metabolites. Probiotics counterbalance the effect of MDD and specifically downregulate downstream metabolites of the kynurenine pathway.